2021
DOI: 10.1155/2021/2976351
|View full text |Cite
|
Sign up to set email alerts
|

Universal Evolutionary Model for Periodical Species

Abstract: Real-world examples of periodical species range from cicadas, whose life cycles are large prime numbers, like 13 or 17, to bamboos, whose periods are large multiples of small primes, like 40 or even 120. The periodicity is caused by interaction of species, be it a predator-prey relationship, symbiosis, commensalism, or competition exclusion principle. We propose a simple mathematical model, which explains and models all those principles, including listed extremal cases. This rather universal, qualitative model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(39 reference statements)
0
2
0
1
Order By: Relevance
“…Te present research also provides a basis for future work to consider whether nondeliberate processes can produce Ulam's spiral, thus providing an assessment of whether an allocation of cooperators in the fashion depicted in this paper is empirically plausible. Past research has shown how physical [97,98], biological [1,[99][100][101][102][103][104][105][106][107], and social phenomena [2,3] can draw attention to the prime numbers and foundational studies in this avenue of research have considered how prime-generating patterns might infuence the spatial organization of entities [1]. Te present paper underscores the importance of such work and it calls for further investigation into how or whether Ulam's spiral can emerge in reality-not just on the theoretician's page-as a spatial distribution of organisms capable of stimulating cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Te present research also provides a basis for future work to consider whether nondeliberate processes can produce Ulam's spiral, thus providing an assessment of whether an allocation of cooperators in the fashion depicted in this paper is empirically plausible. Past research has shown how physical [97,98], biological [1,[99][100][101][102][103][104][105][106][107], and social phenomena [2,3] can draw attention to the prime numbers and foundational studies in this avenue of research have considered how prime-generating patterns might infuence the spatial organization of entities [1]. Te present paper underscores the importance of such work and it calls for further investigation into how or whether Ulam's spiral can emerge in reality-not just on the theoretician's page-as a spatial distribution of organisms capable of stimulating cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo tanto, los ciclos de floración parecen estar agrupados estrechamente en números que se pueden factorizar en pequeños números primos (Goles et al 2021). Veller et al (2015) propusieron un modelo matemático simple para explicar la evolución de los intervalos de floraciones masivas de los bambúes.…”
Section: ₂₆₀ C G�������� � As V���unclassified
“…Recent theoretical models [ 35 , 36 ] add both to this list of ways that cooperation can evolve and to the academic variety of this research area. The models show that cyclical behaviour on prime-number period lengths (as observed in predator–prey models predicting prime-valued prey life cycles [ 37 , 38 ]) can instigate cooperation’s evolution by allowing cooperators to evade defectors who spread themselves across a large number of composite time points [ 35 , 36 ]. Such findings establish how a formative mathematical construct (the prime numbers) connects to models of cooperation as foreshadowed in past research [ 37 ], thus branching off from a more general line of inquiry that studies the mathematical underpinnings of moral behaviour (i.e.…”
Section: Introductionmentioning
confidence: 99%